Screening of the antioxidant and antibacterial effects of extracted essential oils from Thunbergia coccinea, Acacia polyacantha, Polygonum micrpcephallum, Abies spectabilis and Clerodendrum colebrookianum - Zaman, Gaffar Sarwar; Alshahrani, Mohammad Y.; Barua, Pranab; Aladel, Alanoud; Zaman, Forhad Akhtar; Ahmad, Irfan; Khan, Mohammad Idreesh; Snoussi, Mejdi; Saeed, Mohd (Cellular and Molecular Biology, 2022)
During the previous few decades, it has been seen that there is a rapid emergence of pathogens resistant to multiple antibiotics. This has now become a global crisis. Some unexplored or less explored plants also provide some antibacterial, bactericidal and antioxidant properties. The antibacterial, bactericidal effects of extracted essential oils (EEOs) of Thunbergia coccinea, Acacia polyacantha, Polygonum micrpcephallum, Abies spectabilis and Clerodendrum colebrookianum was tested in comparison with standard antibiotics. The methods chosen were disc diffusion and deduction of minimum inhibitory concentration (MIC) by microbroth dilution assays of the EEOs against the bacterial strains.The antioxidant activity was found out utilizing DPPH free radical scavenging assay, MDA, Hydrogen peroxide radical inhibition assay and Superoxide radical inhibition assay (O 2 -). Some commonly used standard antibiotics (metronidazole, amoxicillin, clarithromycin, rifampicin, clindamycin and oxacillin,) were utilized to compare the EEO antibacterial action. Clerodendrum colebrookianum (85.17 ± 3.06 µg MDA/g extract) had a reasonable MDA. Acacia polyacantha in MIC had values of 3.86 ± 0.25 to 6.20 ± 0.16. Polygonum micrpcephallum had excessive H2O2 (48.27 ± 2.4 5%). The antibacterial actions determined by the paper disc‑diffusion technique of the EEO extracted from these plants showed that most had some antibacterial actions. Also, it was seen that the bactericidal action of the EEO extracted from E. alba was most potent against S. pyogenes (4.06 ± 0.15). The extract of the plant at varying concentrations (20, 40, 60, 80 and100 mg/mL) demonstrated noteworthy (P< 0.001) anthelmintic action in an effective change when the dose was adjusted. In conclusion, most of the tested plants contain a medicinal value, which can be utilized in the future to supplement artificial medicines and cure emerging diseases that create havoc for mankind.